2017
DOI: 10.1155/2017/5398542
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Protects against MPP+‐Induced Neuronal Injury through DJ‐1‐Nrf2 Antioxidant Pathway

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder. We have found that salidroside (Sal) exhibited neuroprotective effects against MPP+ toxicity. However, the molecular mechanism is not fully understood. In this study, we found that Sal significantly prevented MPP+-induced decrease of mRNA and protein expression of Nrf2, GCLc, SOD1, and SOD2 in SH-SY5Y cells. Moreover, silencing of Nrf2 significantly inhibited Sal-induced increase in mRNA and protein expression of GCLc, SOD1, and SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(36 reference statements)
3
9
0
Order By: Relevance
“…DJ-1 acts as a chaperone and protease to stabilize mitochondria and protect cells from oxidative stress ( 344 ). Several other cellular functions have been attributed to DJ-1, including; binding of Ras as a transcriptional co-activator ( 345 ), negative regulation of the phosphoinositide-3-kinase (PI3K)/AKT signaling cascade through inhibition of PTEN ( 309 , 346 , 347 ), chaperone function ( 348 , 349 ), and RNA binding ( 350 ). Although controversial, DJ-1 has also been claimed to have glyoxalase ( 351 ) and deglycase ( 352 ) enzyme activities ( 353 ).…”
Section: Metformin: Mechanism Of Action In Neurodegenerative Diseasesmentioning
confidence: 99%
“…DJ-1 acts as a chaperone and protease to stabilize mitochondria and protect cells from oxidative stress ( 344 ). Several other cellular functions have been attributed to DJ-1, including; binding of Ras as a transcriptional co-activator ( 345 ), negative regulation of the phosphoinositide-3-kinase (PI3K)/AKT signaling cascade through inhibition of PTEN ( 309 , 346 , 347 ), chaperone function ( 348 , 349 ), and RNA binding ( 350 ). Although controversial, DJ-1 has also been claimed to have glyoxalase ( 351 ) and deglycase ( 352 ) enzyme activities ( 353 ).…”
Section: Metformin: Mechanism Of Action In Neurodegenerative Diseasesmentioning
confidence: 99%
“… 29 , 52 More recently, salidroside (25–100 μM) was also reported to significantly reduce MPP + -induced neuronal injury via DJ-1 -Nrf2 antioxidant pathway in SH-SY5Y cells. 53 Besides, it was demonstrated that salidroside (100 μg/mL) could induce the differentiation of rat mesenchymal stem cells (MSCs) to dopaminergic neurons with increased DA release. 54 Salidro-side was also reported to protect primary cortical neurons and SN4741 cells from endoplasmic reticulum (ER) stress.…”
Section: Pharmacological Activity and Mechanisms Of Actionmentioning
confidence: 99%
“…ARE is located in the promoter region of several genes encoding various antioxidant enzymes [ 78 ]. Silencing of Nrf2 significantly inhibits mRNA and protein expression of SOD1, and SOD2 [ 79 ]. We suppose that degradation of Nrf2 via the phosphorylation by GSK-3β may lead to a similar result ( Figure 3 ).…”
Section: Suggestions Of Pi3k/akt/pten Signaling On Sod Expressionmentioning
confidence: 99%